PEMIKIRAN AHMAD SYAFII MAARIF TERHADAP KEDUDUKAN PEREMPUAN DALAM POLITIK - Fatmawati Fatmawati; Latifah Anwar (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This paper aims to examine the views of Ahmad Syafii Maarif on the position of women in politics according to Islamic teachings. The data were collected from his two books 'Islam dalam Bingkai Keindonesiaan dan Kemanusiaan: Sebuah Refleksi Sejarah' revised edition and 'Titik-Titik Kisar di Perjalananku: Autobiografi Ahmad Syafii Maarif'. The findings show that his family background and education have formed his concern to the position of women in family, society, and politics as well as women’s rights according to Islamic teachings. In Islam, the position of women and men are equal. Women have the same rights to be political leaders as men. In politics, women are entitled to become leaders on the conditions that (1) they have excellent abilities; (2) moral, which is pious and upholding justice; (3) (preferably) over 40 years of age; and (4) obtaining husband's permission.